2010
DOI: 10.1158/0008-5472.can-09-2554
|View full text |Cite|
|
Sign up to set email alerts
|

Combining Human and Rat Sequences in Her-2 DNA Vaccines Blunts Immune Tolerance and Drives Antitumor Immunity

Abstract: Immune tolerance to tumor-associated self-antigens poses a major challenge in the ability to mount an effective cancer vaccine response. To overcome immune tolerance to HER-2, we formulated DNA vaccines that express both human HER-2 and heterologous rat Neu sequences in separate plasmids or as single hybrid constructs that encode HER-2/Neu fusion proteins. Candidate vaccines were tested in Her-2 transgenic (Tg) mice of BALB/c (BALB), BALB/c × C57BL/6 F1 (F1), or C57BL/6 (B6) background, which exhibit decreasin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…Initial studies found cryoablation, with or without CpG injection, insufficient to induce α-neu Ab, consistent with immune tolerance to neu (not shown). As in breast cancer patients, moderate α-neu immunity can be induced in NeuT mice by DNA vaccination (43, 44). Therefore, we tested if cryoablation impacts vaccine induced immunity in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies found cryoablation, with or without CpG injection, insufficient to induce α-neu Ab, consistent with immune tolerance to neu (not shown). As in breast cancer patients, moderate α-neu immunity can be induced in NeuT mice by DNA vaccination (43, 44). Therefore, we tested if cryoablation impacts vaccine induced immunity in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained from transgenic mouse models demonstrated that vaccination with DNA plasmids coding for xenogeneic HER2 elicited a strong immunologic response without cross-reaction (16). Chimeric rat/human HER2 plasmids were most effective in blunting immune tolerance to both rat and human HER2, suggesting that the presence of heterologous regions enhances immunogenicity against the antigen (17,18). Thus, the self-sequence ensures the specificity of the immune response, whereas the xenogeneic part circumvents immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric vaccines containing both self-human HER2 and heterologous rat neu DNA sequences induced a more potent cellular and humoral antitumor immunity than selfsequence alone (17,18). However, no data on their potential efficacy in humans are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…HER2/neu has been targeted using polynucleotide or DNA vaccine strategies involving both syngeneic and xenogeneic sequences, the latter to improve the magnitude of elicited immune responses [246][247][248][249][250][251][252][253][254], in prime boost strategies combining DNA vaccines with viral vector-based vaccines [255] and with gene-modified allogeneic cellular vaccines (NCT00095862) [256]. Viral vector vaccine strategies using adenovirus vectors [257][258][259][260], alphavirus vectors [212,213,261], vaccinia virus vectors (NCT00485277 and NCT01152398), vesicular stomatitis virus [262] and polyoma virus systems [263,264] have all been used to elicit anti-HER2/neu immune responses.…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%